Tourist motivations and golf course attributes for the practice of golf tourism in Portugal - Cristóvão, Carolina Henriques Micaelo de Sequeira (2022)
In Portugal, regarding the golf tourists’ main motivations and golf course attributes, research in this area is still limited. Thus, the main aim of this study is to analyse the influence that golf courses have on choices made by golf tourists related to their travel destination, through the analysis of the tourism motivation factors and golf course attributes, and which ones are fundamental to the golfers’ choice of where to play golf. It seeks to identify these motivations and the more relevant golf course attributes and, by doing so, to contribute to the market knowledge in terms of golfers' needs and preferences. In order to draw some relevant conclusions from this research, a survey was conducted, which obtained 214 valid answers given by golf tourists who have previously played the sport in Portugal. Furthermore, after all the information and data obtained were analysed, the findings of this study revealed that there are five motivational dimensions (“Nature and Leisure”, “Escape and Relaxation”, “Learning and Challenging”, “Family Togetherness” and “Business Opportunity”) and three golf course attributes dimensions (“Golf Course Characteristics and Game Conditions”, “Access and Logistics” and “Leisure Infrastructures”) important for golf tourists when choosing a place to play golf in Portugal. Lastly, the golf tourist was defined by three clusters in terms of golf tourism motivations (the “Leisure Golf Tourist”, the “Skilled Focused Golf Tourist” and the “Social Golf Tourist”) and by two clusters for the preferable golf course attributes (the “Technical Golf Tourist” and the “Householder Golf Tourist”).